Identification of locally advanced rectal cancer-related genes based on transcriptome and mendelian randomization analysis with biological validation - Lao, Tianhao; Yang, Jie; Wang, Jie; Wang, Yongqiang; Ma, Qianyun; Chen, Hua (Frontiers in Immunology, 2025)
BackgroundColorectal cancer remains one of the leading causes of cancer-related mortality worldwide, with locally advanced rectal cancer (LARC) representing a particularly challenging clinical subset. Deciphering the molecular mechanisms of LARC is essential for the development of more effective and personalized therapeutic strategies.MethodsGene expression profiles from the Gene Expression Omnibus (GEO) database were analyzed to identify differentially expressed genes (DEGs) in LARC. Mendelian randomization (MR) analysis was subsequently performed using publicly available eQTL data to assess potential causal relationships between these DEGs and LARC. External validation of DEGs was conducted using data from the Cancer Genome Atlas (TCGA). Enrichment analyses were further conducted to explore the biological significance. To characterize the immunological landscape of LARC, immune cell infiltration and scRNA-seq analyses were employed. Survival analysis was conducted to evaluate the prognostic relevance. Finally, functional assays were performed on selected gene to validate its roles in LARC pathogenesis in vitro.ResultsA total of 1, 113 upregulated and 1, 233 downregulated genes were identified in LARC. MR analysis, combined with external TCGA validation, revealed 9 significant co-expressed genes (CEGs) potentially involved in LARC pathogenesis. These CEGs were primarily enriched in pathways related to immune regulation, oxidative stress response, ERK1/ERK2 and JAK-STAT signaling, as well as cancer metabolism and therapeutic resistance. Immune infiltration and scRNA-seq analyses revealed notable alterations in the tumor microenvironment and distinct expression patterns of the CEGs. Notably, in vitro functional assays of the less-reported gene SLC19A1 demonstrated its role in promoting LARC progression.ConclusionThis study offers new insights into the molecular mechanisms underlying LARC pathogenesis and identifies potential therapeutic targets.